2013
DOI: 10.1111/desc.12057
|View full text |Cite
|
Sign up to set email alerts
|

Mapping subcortical brain maturation during adolescence: evidence of hemisphere‐ and sex‐specific longitudinal changes

Abstract: Early to mid-adolescence is an important developmental period for subcortical brain maturation, but longitudinal studies of these neurodevelopmental changes are lacking. The present study acquired repeated magnetic resonance images from 60 adolescent subjects (28 female) at ages 12.5 and 16.5 years to map changes in subcortical structure volumes. Automated segmentation techniques optimized for longitudinal measurement were used to delineate volumes of the caudate, putamen, nucleus accumbens, pallidum, hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
140
7
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 125 publications
(179 reference statements)
30
140
7
6
Order By: Relevance
“…Despite this limitation, the current sample of 140 youth is signifi cantly larger than some of the other published neuroimaging studies of subcortical brain volume in familial alcoholism (Benegal et al, 2007;Hanson et al, 2010;Hill et al, 2001). As previously noted, the correlation between manual tracing and automated segmentation techniques can be low (Morey et al, 2009), but automated techniques may be advantageous for delineation of small nuclei, such as the ventral striatum, which does not have clear visually demarcated boundaries and was delineated using an automated method in another study of adolescents (Dennison et al, 2013). However, because of the low correlations of automated techniques with manual tracing for subcortical regions, it is possible that relationships between brain volume and risk status for other ROIs in the analysis could have been missed due to insuffi cient reliability of the automated technique.…”
Section: Discussionmentioning
confidence: 88%
“…Despite this limitation, the current sample of 140 youth is signifi cantly larger than some of the other published neuroimaging studies of subcortical brain volume in familial alcoholism (Benegal et al, 2007;Hanson et al, 2010;Hill et al, 2001). As previously noted, the correlation between manual tracing and automated segmentation techniques can be low (Morey et al, 2009), but automated techniques may be advantageous for delineation of small nuclei, such as the ventral striatum, which does not have clear visually demarcated boundaries and was delineated using an automated method in another study of adolescents (Dennison et al, 2013). However, because of the low correlations of automated techniques with manual tracing for subcortical regions, it is possible that relationships between brain volume and risk status for other ROIs in the analysis could have been missed due to insuffi cient reliability of the automated technique.…”
Section: Discussionmentioning
confidence: 88%
“…However, it must be noted that recent research has shown that the brain is not nearly as dichotomous as once thought. So according to the right brain vs left brain theory, for it to appeal to left-brain dominated learners, most of whom are females, (Dennison et al, 2013) the curriculum, its instruction and assessment procedures need to be developed to accommodate left-brain dominant talents and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Algunos de los resultados publicados por el grupo de Sussman son similares a los que encontraron Dennison et al (2013), quienes estudiaron los cambios de maduración en el estriado, globo pálido, hipocampo, amígdala y tálamo durante la adolescencia temprana y media utilizando un diseño longitudinal y consideraron que esta etapa se caracterizaba por cambios sorprendentes en la maduración subcortical del cerebro. En su estudio se adquirieron imágenes de resonancia magnética de 60 sujetos adolescentes (28 mujeres) con un rango de edad 12,5 y 16,5 años.…”
Section: Estudios Posteriores (Infancia-adolescencia)unclassified
“…De forma similar, el hipocampo derecho no era más grande que el izquierdo en la línea de base, pero aumentó más que el izquierdo durante este período de desarrollo para ser significativamente mayor en el seguimiento, lo cual es consistente con los hallazgos de volúmenes del hipocampo derecho mayores en adultos normales (Pedazra, Bowers & Gilmore, 2004). Por tanto, el desarrollo cerebral subcortical desde la adolescencia temprana hasta la adolescencia media se caracteriza por la notable especialización hemisférica y los dimorfismos sexuales, y proporciona un marco para interpretar los cambios típicos y atípicos en la cognición, el afecto y el comportamiento (Dennison et al, 2013).…”
Section: Estudios Posteriores (Infancia-adolescencia)unclassified
See 1 more Smart Citation